Design and Analysis of a Novel Piezo-Actuated XYθz Micropositioning Mechanism with Large Travel and Kinematic Decoupling - Ruijiang Xiao; Shubao Shao; Minglong Xu; Zijian Jing (Advances in Materials Science and Engineering)
A novel hybrid-type XYθz micropositioning mechanism driven by piezoelectric actuators is proposed in this paper. With the purpose of realizing a large motion range and 3-DoF independent motion within a compact size, the mechanism is designed using a symmetric translational part and a rotational part that are linked serially. The translational part is based on a double-amplification mechanism incorporating a guidance mechanism for decoupling; the rotational part uses a nonuniform beam with an amplification mechanism to translate the linear output displacement of piezoelectric actuators into a large rotational angle around the Z axis. To precisely predict the output displacements and implement dimensional design, electromechanical models of the translational mechanism and rotational mechanism are established. According to the theoretical model, dimensional optimization is carried out to achieve large motion ranges within a compact size. A prototype of the proposed mechanism is fabricated according to the optimized results, and the performance of the mechanism is validated by experiment. The experimental results show that translational travel in X and Y directions of 204.2 μm and 212.8 μm, respectively, and travel of 8.7 mrad in the θz direction can be realized in a small size of 106 mm × 106 mm × 23 mm. And, the output coupling was evaluated to be below 3%, indicating an excellent decoupling performance.